Evolution of phenolics and polyphenoloxidase isoenzymes in relation to physical-chemical parameters during loquat (Eriobotrya japonica cv. Algerie) fruit development and ripening - Casado Vela J.; Sellés Marchart S.; Bru Martínez R.; Gómez Lucas I. (First international symposium on loquat, 2003)
Polyphenoloxidase (PPO) and phenolics are directly responsible for the enzymatic browning. In intact cells PPO and its phenolic substrates are physically separated in chloroplasts and vacuoles respectively, precluding oxidation of phenolics and enzymatic browning. Cell disruption by injury or cell disassembly during ripening brings PPO into contact with phenolics and enzymatic browning occurs. In this work, we have monitored the co-evolution of PPO isoenzyme levels and phenolics during loquat cv. Algerie development and ripening, and fruit juice physical-chemical parameters which evolve according to the ripening stage. The onset of ripening is accompanied by a drastic increase of juice pH (0.4 units), sugars and a drastic decrease of acidity while conductivity decreased uniformly during fruit development and ripening. Changes in PPO resemble those of pH, sugars and acidity as judged by drastic changes at onset of ripening, while phenolics increased uniformly during fruit development and ripening.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)